PANJANG PENGANGKURAN DAN JARAK TEPI PADA KUAT TARIK ANGKUR ADHESIF - Christianto, Daniel; Patrick, Patrick; Untari Liucius, Yenny (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Anchors are used to transfer structural loads in tension, shear, or a combination of both. One example of an anchor type is the post-installed adhesive anchor. Post-installed adhesive anchors are installed after the concrete has hardened. The main advantage of post-installed anchors is the flexibility of installation time, which makes it easier to schedule construction activities. One of the factors that determine the tensile strength of an anchor is the embedment depth and edge distance of the anchor in the concrete. Typically, the embedment depth and edge distance used are obtained from the anchor manufacturer's brochure or catalog and are also regulated in SNI 2847:2019. With the advancement of technology and new products from manufacturers, it is necessary to conduct tensile strength tests to compare the results of different embedment depths and edge distances. In this research, tensile tests were conducted on post-installed adhesive anchors with embedment depths of 35 mm, 105 mm, and 150 mm, with edge distances of 75 mm, 130 mm, and 250 mm at each depth. From the test results, it can be concluded that the embedment length of the anchor affects the tensile strength, as deeper embedment results in greater tensile strength for the anchor. Abstrak Angkur digunakan untuk menyalurkan beban struktural dalam tarik, geser atau kombinasi antara tarik dan geser. Salah satu contoh jenis angkur adalah angkur pasca pasang adhesif. Angkur pasca pasang adhesif adalah jenis angkur yang di pasang setelah beton mengeras. Keunggulan utama angkur pasca pasang adalah adalah fleksibilitas waktu pemasangan sehingga memudahkan mengatur jadwal konstruksi. Salah satu faktor yang menentukan kuat tarik pada angkur adalah kedalaman penanaman angkur dan juga jarak tepi angkur pada beton. Umumnya kedalaman penanaman angkur dan jarak tepi yang digunakan didapatkan dari brosur atau katalog pabrik angkur itu sendiri dan juga diatur dalam SNI 2847:2019 dengan berkembangnya teknologi dan produk-produk baru dari manufaktur perlu adanya uji kekuatan tarik untuk membandingkan hasil kekuatan tarik yang diperoleh dengan kedalaman penanaman dan jarak tepi yang berbeda-beda. Pada penelitian ini dilakukan pengujian tarik pada angkur pasca pasang adhesif dengan kedalaman penananaman sebesar 35 mm, 105 mm dan 150 mm dengan jarak tepi 75 mm, 130 mm dan 250 mm pada masing-masing kedalaman. Dari hasil pengujian dapat disimpulkan bahwa kedalaman penanaman angkur mempengaruhi hasil kuat tarik, semakin dalam penanaman angkur maka semakin besar kuat tarik dari angkur tersebut.